Citizen Cash the political life and times of Johnny Cash - Foley, Michael Stewart (Basic Books, 2021)
"Johnny Cash was an American icon, known for his level bass-baritone voice and somber demeanor, for huge hits like 'Ring of Fire' and 'I Walk the Line.' He's one of the best-selling musicians of all time, and his crossover appeal earned him inductions into the Country Music, Gospel Music, and Rock and Roll Halls of Fame. But he was also the most prominent political artist in the United States, even if he wasn't recognized for it in his own lifetime, or since his death in 2003. Then and now, people have misread Cash's politics, usually accepting the idea of him as a 'walking contradiction.' Cash didn't fit into easy political categories--liberal or conservative, Red state or Blue state, hawk or dove. Like most people, Cash's politics were remarkably consistent in that they were based not on ideology or scripts--but on emotion, instinct, and identification. He supported Richard Nixon in his Vietnam War policies, while also seeming to stand up both for those asked to fight the war and for those who protested against it. Instead of choosing sides, Cash channeled an emotional discontent that bridged America's youth and the 'silent majority.' Foley traces the political evolution of the Man in Black as a prominent public citizen. Drawing on untapped archives and new research on social movements and grassroots activism, Citizen Cash offers a major reassessment of a legendary figure"--
Keywords: Cash, Johnny -- 1932-2003; Politisches Denken; Cash, Johnny / Criticism and interpretation; Cash, Johnny / Political activity; Cash, Johnny / Political and social views; Country music / Political aspects / History / 20th century; MUSIC / History & Criticism; Cash, Johnny; Political and social views; Political participation; 1900-1999; Biographies; Criticism, interpretation, etc; History